HOW ARE DYNAMIC CAPABILITIES AND DIGITAL MARKETING RELATED? A REFLECTION FROM LITERATURE - Gutierrez-Leefmans, Catalina (2019)
This study aims to explore the relationship between dynamic capabilities and digital marketing. From the literature review on dynamic marketing capabilities, marketing capabilities and digital marketing capabilities it is inferred that without considering the denomination, they all include the dynamic component factors. The review also results on the consideration that these capabilities already involve the use of ICTs and digital tools for their development. It is concluded that digital marketing directly supports the marketing capabilities required by the context and therefore the business strategy directed to a better performance of firms.